Application of agro–waste materials for improved performance of water–based drilling fluid (2021)
Bio–resources and its derivatives have distinctive potential in various industrial applications and solutions especially for captivating usage in drilling fluid formulations for the petroleum industry. Drilling fluids formulations have tremendously advanced through increasing research and development of unique additives to improve their functionalities and meet specific properties in well design operations. In this article, water–based mud formulated with powdered and ash products derived from plantain and banana peels were evaluated. The effects of varying concentrations of these additives and the blends on the performance of the mud were examined by comparison with Low Viscosity Sodium Carboxymethyl Cellulose (LV CMC) for rheology and sodium hydroxide (NaOH) for pH control. The rheology of the mud improves with increasing concentration of the powdered products in a way similar to that of LV CMC. However, powdered banana peels most effectively improved the rheology of the mud to attain 10cp plastic viscosity (PV), 13lb/100sq.ft yield point (YP), 16lb/100sq.ft and 23lb/100sq.ft gel strength at 10seconds and 10minutes, respectively. Plantain peel ashes compared favourably with NaOH in controlling the pH of the mud. Further modification of the products to achieve the same properties as LV CMC is recommended in subsequent studies.